Study of the spicy porridge tradition at the early Ramadhan in the Malay community - M. Nasihudin Ali (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Indonesia is a diverse country with numerous tribes and cultures, and the local culture greatly influences society, particularly in religious practices. The relationship between culture, local traditions, and Islam is vital for acceptance and influence within communities, as seen in the example of the spicy porridge tradition among the Malay community during Ramadan in North Sumatra. Several ingredients are used in making spicy porridge, including vegetables, tubers, nuts, and other ingredients. This study aims to explain the background of the spicy porridge tradition and the meaning of the spicy porridge tradition for the Malay community. The method used in this study is qualitative-descriptive research. The purpose of using a qualitative method is to emphasize that spicy porridge is Malay food served during Ramadan. It is because it is complicated and takes a long time to make it. In addition, the Malay communities’ habit of serving spicy porridge is only during Ramadan. Meanwhile, the benefits of spicy porridge itself are to warm and nourish the body because it consists of ingredients such as spices and vegetables. Additionally, it highlights the importance of the essence and authenticity of the dish, emphasizing the value of community interaction in its preparation.